Conversores abaixador série-paralelo CC-CC e CA-CC a capacitor chaveado - Menegatti, Ricardo Brancalione (2021)
This work presents the study of a series-parallel switched capacitor step-down converter with static voltage gain of 1/2. The concepts, definitions and operating principle as a DC-DC and AC-DC converter are presented. A proposal for the formalization of operating modes (continuous current conduction mode in switched capacitors and discontinuous conduction mode) for the DC-DC converter based on the converter operation steps is presented. Features, waveforms, and design considerations for the two conduction modes are presented. Are also presented a detailed design methodology, evaluated the converter’s output power regulation, and implemented a 30 W DC-DC laboratory prototype to validate the proposal, with efficiency of 87,90%. Furthermore, the study of the operation as an AC-DC converter is presented, operating in power factor correction for the two different conduction modes. An approximately 43 W AC-DC laboratory prototype is designed and implemented using the 127 VRMS distribution network as the input source, with an efficiency of approximately 80% and a power factor of 0,79.